2001
DOI: 10.1074/jbc.m008902200
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Receptor Oligomerization Using Time-resolved Fluorescence Resonance Energy Transfer and Bioluminescence Resonance Energy Transfer

Abstract: ]enkephalin nor the inverse agonist ligand ICI174864 were able to modulate the oligomerization status of this receptor. Interactions between co-expressed ␦-opioid receptors and ␤ 2 -adrenoreceptors were observed in co-immunoprecipitation studies. Such hetero-oligomers could also be detected using bioluminescence resonance energy transfer although the signal obtained was substantially smaller than for homo-oligomers of either receptor type. Signal corresponding to the ␦-opioid receptor-␤ 2 -adrenoreceptor heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(78 citation statements)
references
References 36 publications
5
71
0
Order By: Relevance
“…Energy transfer levels detected were very similar to those observed for the ␤2AR-YFP/␤2AR-Rluc couple (Fig. 2a) previously shown to form constitutive oligomers (7,9,10). Significant BRET between MT1R-Rluc and MT2R-YFP (Fig.…”
Section: Detection Of Mt1r and Mt2r In Hek 293supporting
confidence: 65%
See 2 more Smart Citations
“…Energy transfer levels detected were very similar to those observed for the ␤2AR-YFP/␤2AR-Rluc couple (Fig. 2a) previously shown to form constitutive oligomers (7,9,10). Significant BRET between MT1R-Rluc and MT2R-YFP (Fig.…”
Section: Detection Of Mt1r and Mt2r In Hek 293supporting
confidence: 65%
“…The second model proposes that GPCR are constitutively oligomerized and is supported by studies reporting high basal BRET or FRET signals for ␣-mating factor (6), ␤2-adrenergic (␤2AR) (7), tyrothropin-releasing hormone (8), ␦-opioid (9), type A cholecystokinin (10), and dopamine D2 receptors (11). Agonist-promoted increases in signals were observed in some of these cases (7,8,11) but not in others (6,9), leading some investigators to suggest that ligand-induced changes in constitutive BRET or FRET could result from conformational changes in pre-existing receptor oligomers rather than from ligand efficacy-related regulation of the oligomerization state (2,7). If ligand-promoted increases in BRET or FRET reflect changes in oligomerization that are linked to the receptor activation state, one would predict that ligands with different efficacies would lead to distinct changes in energy transfer.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…This shows that the coil-coiled domains in the C-terminal tails of these subunits strongly stabilize the heterodimer. We therefore conducted TR-FRET experiments as described previously (40). In this assay, a FRET signal is measured at the surface of intact COS-7 cells between a donor molecule (europium cryptate-pyridine bipyridine) linked to an anti-HA monoclonal antibody and an acceptor molecule (Alexa Fluor® 647) linked to an anti-c-Myc monoclonal antibody (Fig.…”
Section: Gb2 Increases Agonist (But Not Antagonist) Affinity Inmentioning
confidence: 99%
“…Heterodimerization of opioid receptors and ␦ results in novel ligand binding and function, proving that GPCR oligomerization has physiologic relevance (12). More recently, energy transfer studies, using either fluorescence (FRET) or bioluminescence (BRET), have also shown the proximity of monomers of many members of the rhodopsin family of GPCRs, including ␤ 2 -adrenergic receptor (13), somatostatin receptors (14), opioid receptors (15), and the C5a receptor (57).…”
mentioning
confidence: 99%